Chalcogenides Metastability and Phase Change Phenomena - Kolobov, Alexander V.; Tominaga, Junji (Springer Series in Materials Science, 2012)
A state-of-the-art description of metastability observed in chalcogenide alloys is presented with the accent on the underlying physics. A comparison is made between sulphur(selenium)-based chalcogenide glasses, where numerous photo-induced phenomena take place entirely within the amorphous phase, and tellurides where a reversible crystal-to-amorphous phase-change transformation is a major effect. Applications of metastability in devices¿optical memories and nonvolatile electronic phase-change random-access memories among others are discussed, including the latest trends. Background material essential for understanding current research in the field is also provided.